Ammonia and Nitrate Removal in Refinery Wastewater using Aerobic Treatment Systems - Aimran Bin Abd Hamid, Aimran (Universiti Teknologi Petronas, 2010)
The project comprises of two phases. The first phase focuses on the degradation of ammonia and nitrate in refinery wastewater using the Sequencing Batch Reactor treatment system. In this phase experiment were conducted by using 4 setup of SBR reactors consisting on different wastewater and the control of air into the reactors.